2014
DOI: 10.1007/s10549-014-3180-7
|View full text |Cite|
|
Sign up to set email alerts
|

A novel vaccinia virus with dual oncolytic and anti-angiogenic therapeutic effects against triple-negative breast cancer

Abstract: Purpose Vascular endothelial growth factor (VEGF) expression is higher in triple-negative breast cancers (TNBC) compared to other subtypes and is reported to predict incidence of distant metastases and shorter overall survival. We investigated the therapeutic impact of a vaccinia virus (VACV) GLV-1h164 (derived from its parent virus GLV-1h100), encoding a single-chain antibody (scAb) against VEGF (GLAF-2) in an orthotopic TNBC murine model. Methods GLV-1h164 was tested against multiple TNBC cell lines. Viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 24 publications
(30 reference statements)
0
39
0
Order By: Relevance
“…In the tumor, NO was shown to be both friend and foe [5, 14]. It is believed that by producing variable levels of NO, iNOS can orchestrate various functions in different microenvironments [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tumor, NO was shown to be both friend and foe [5, 14]. It is believed that by producing variable levels of NO, iNOS can orchestrate various functions in different microenvironments [15].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, preclinical and clinical studies have demonstrated that various VACVs have a broad spectrum of anticancer activity and good safety [2]. Tumor-targeting mechanisms of VACV include virus-mediated direct oncolysis, antivascular effects and induction of antitumor immune responses [35]. The latter mechanism of action might be essential in the elimination of tumor cells which are able to escape virus infection [6].…”
Section: Introductionmentioning
confidence: 99%
“…The cancer cells infected by these viruses are induced for self-destruction by apoptosis or killed by autophagy and necrosis. After infection, viruses typically inactivate the cellular regulatory mechanisms and take control of the cancer cell oncolytic function has been shown to be able to kill the TNBC cell lines in a dose-dependent fashion (Gholami et al, 2014). GLV-1h153…”
Section: Trail Death Receptor Dr5 Dna Vaccinementioning
confidence: 99%
“…is another vaccinia oncolytic virus which has been shown to be effective in TNBC and mTNBC (Gholami et al, 2014).…”
Section: Trail Death Receptor Dr5 Dna Vaccinementioning
confidence: 99%
“…SQPV was isolated from a grey squirrel (Sciurus carolinensis) in Maryland in 1953 and initially placed into the genus Leporipoxvirus by Kilham et al (1953); it was later thought to be a member of the genus Parapoxvirus (Housawi et al, 1998), but a sub- (Chen et al, 2001;Zhang et al, 2007;Kochneva et al, 2012;Chan and McFadden, 2014) Breast tumor model, Ovarian tumor model, etc (Hung et al, 2007;Zhang et al, 2007;Hiley et al, 2010;Gholami et al, 2014) Various solid tumors, Breast cancer (Gentschev et al, 2014;Mell et al, 2014) GLV-1h68*, GLV-1h99, GLV-1h108, VV-mIL2, VVhEA, VV-hup53, etc Wyeth Attenuated, transgenes inserted (Mastrangelo et al, 1999;Liu et al, 2014) Melanoma model, Bladder cancer model, etc (Mastrangelo et al, 1999;Gomella et al, 2001) Melanoma cancer, Liver cancer, etc (Mastrangelo et al, 1999;Park et al, 2008;Heo et al, 2013) JX-594* WR Attenuated, transgenes inserted (Gnant et al, 1999;McCart et al, 2001;Thorne et al, 2007;Parviainen et al, 2015) Colon cancer model. etc (Gnant et al, 1999;McCart et al, 2001;Autio et al, 2014) Various tumors (Zeh et al, 2015) JX-795, JX-963*, vvDD*, VV-TRAIL, etc MVA Severely attenuated, transgenes inserted (Sutter and Moss, 1992;Kochneva et al, 2012) Various cancer model (Drexler et al, 1999;Carroll et al, 1997) Various tumors (Larocca and Schlom, 2011;Amato et al, 2012;Gómez et al, 2013) MVA-5T4*, MVAhup53…”
Section: Origin Of Oncolytic Poxvirusesmentioning
confidence: 99%